Endophthalmitis: a bibliometric study and visualization analysis from 1993 to 2023 - Fu, Xiangyu; Du, Wenyu; Huang, Ling; Ren, Xiang; Chen, Danian (Frontiers in Cellular and Infection Microbiology, 2024)
AimsThis study is designed to generalize and depict the research hotspots of endophthalmitis through bibliometric methods and software and analyze the evolutive tendency of the work on this severe disease over the past 30 years.MethodsThis study employed a rigorous bibliometric approach. We identified all endophthalmitis-related literature by conducting a comprehensive search of the Science Citation Index Expanded database under the Web of Science Core Collection. The data was then analyzed and visualized using CiteSpace and VOSviewer, two widely recognized software tools in the field of bibliometrics. CiteSpace was used to analyze the country distributions, dual map overlay of journals, keyword bursts, and co-cited references. VOSviewer was employed to describe the authors and co-cited authors, the journals, the co-cited journals, and the keywords co-occurrence network. This robust methodology ensures the reliability and validity of the study’s findings.ResultsA total of 2960 publications, including 2695 articles and 265 reviews, were included in this bibliometric study. There has been no shortage of endophthalmitis-related publications since 1993, with an apparent upward trend during recent years. Possible correlations with the COVID-19 pandemic are also analyzed. These studies were finished by 11,048 authors from 75 countries worldwide, with the United States in the lead. In the keyword co-occurrence network, except for the endophthalmitis term, cataract surgery becomes the keyword with the highest frequency. Different categories of endophthalmitis, including postoperative, post-injection, post-traumatic, and endogenous endophthalmitis, and antibacterial and anti-inflammatory therapies of infectious endophthalmitis, are discussed by categories. From the perspective of the timeline, postoperative and post-injection endophthalmitis were the dominant forms before and after the year 2000, respectively. Co-citation analyses reveal that the Endophthalmitis Vitrectomy Study (EVS) conducted in 1995 provides pivotal guidance for later research. Diverse pathogenic bacteria (e.g., Coagulase-negative Staphylococci, Propionibacterium acnes, Viridians Streptococci, and Bacillus cereus) or fungi (e.g., Candida, Aspergillus, and Fusarium) contribute to varying treatment principles and clinical prognosis, which should be taken seriously. In addition, intravitreal and intracameral antibiotics are the mainstay for treating and preventing infectious endophthalmitis, respectively.ConclusionOur bibliometric analysis provides an overview of dynamic evolution and structural relationships in the research field of endophthalmitis. The displayed hotspots and developmental directions have reference values for future investigation.